Complex Evaluation of Business Macro Environment Components and Factors - Žvirblis, Algis (Ekonomika, 2007)
The presented principles and methods, as well as the basic adoptive models for a complex qualitative analysis and quantitative evaluation of business macro environment components and factors, the results of quantitative evaluation of transport services companies’ macro environment are discussed. In the analysis of business macro environment, the me thud of comprehensive qualitative analysis of macro environment components prevails, including political. legal, social-cultural, economic, scientific-technological and natural components (PEST analysis, PESTEL analysis, Environment Dynamics analysis, scenario analysis). When developing the theoretical basis, it is expedient to solve the tasks of quantitative evaluation conceptually. In the article, problems of the theory and practice of the quantitative evaluation of business macro environment are reflected. A methodology of complex macro environment evaluation is presented. It includes methods of qualitative analysis and quantitative evaluation. The system of quantitative evaluation includes the primary factors, the macro environment components (their integrated indices), as well as a complex evaluation of the macro environment level (in points). It is based on identification of the macro environment factors. qualitative analysis of primary factors and quantitative evaluation using multi criteria methods (in particular, the Simple Additive Weighting (SAW) method). The basic models of macro environment components as well as the common model of the total macro environment (as a composition of components) were elaborated employing the formalisation procedure. The methodology allows to analyse the influence of significant factors and to use the results as emerging new opportunities. The aim of the paper is also to analyse and evaluate the macro environment of Lithuanian transport companies. Analysis, identification and complex evaluation of the road transport services macro environment (its components and primary factors) shows that a favourable influence on their marketing strategy had the political environment. The social environment had an unfavourable impact on the strategic decisions. As the positive factors the economic growth, road infrastructure are indicated, while the negative factors include petrol prices, EURO-2 standards. The methodology of a complex macro environment evaluation may he used for the quantitative macro environment evaluation of the other sectors of Lithuanian economy.